Self-assembling Venturi-like peptide nanotubes. Issue 2 (14th December 2016) - Fuertes, Alberto; Ozores, Haxel Lionel; Amorín, Manuel; Granja, Juan R.
Abstract : The synthesis of Venturi-like peptide nanotubes with precisely controlled dimensions is described. Abstract : We describe the design and synthesis of self-assembling peptide nanotubes that have an internal filter area and whose length and internal diameters, at the entrance and in the constricted area, are precisely controlled.